2012
DOI: 10.1126/science.1217529
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation-Driven Deformations in Graphene

Abstract: The movement of dislocations in a crystal is the key mechanism for plastic deformation in all materials. Studies of dislocations have focused on three-dimensional materials, and there is little experimental evidence regarding the dynamics of dislocations and their impact at the atomic level on the lattice structure of graphene. We studied the dynamics of dislocation pairs in graphene, recorded with single-atom sensitivity. We examined stepwise dislocation movement along the zig-zag lattice direction mediated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
349
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(370 citation statements)
references
References 47 publications
(48 reference statements)
18
349
2
1
Order By: Relevance
“…These defects arise in graphene or in graphitic nanostructures during defective growth and can also be created artificially by means of ion irradiation. [7][8][9][10][11][12][13][14] Their structural details can be directly observed by means of several experimental techniques such as transmission electron microscopy (TEM) [15][16][17][18][19] and scanning tunneling microscopy (STM). 20,21 Because of the occurrence of dangling bonds the defect structure will be associated with a high polyradical character with a multitude of closely spaced locally excited electronic states possessing different spin multiplicities which make their theoretical description very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…These defects arise in graphene or in graphitic nanostructures during defective growth and can also be created artificially by means of ion irradiation. [7][8][9][10][11][12][13][14] Their structural details can be directly observed by means of several experimental techniques such as transmission electron microscopy (TEM) [15][16][17][18][19] and scanning tunneling microscopy (STM). 20,21 Because of the occurrence of dangling bonds the defect structure will be associated with a high polyradical character with a multitude of closely spaced locally excited electronic states possessing different spin multiplicities which make their theoretical description very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hashimoto et al 8 showed the appearance of a dislocation in sp 2 -hybridized carbon, and Warner et al 9 presented atomically resolved aberration-corrected highresolution TEM (AC-HRTEM) images of dislocations in graphene, demonstrating the basic glide and climb steps. In both works, the appearance of the dislocations was attributed to displacement and reorganization of carbon atoms.…”
mentioning
confidence: 99%
“…Atomic-resolution observation of two-dimensional materials and in-situ studies in the TEM require optimization of the electron-optical conditions over a large field of view, for example to understand point defects, dislocations and distortions of the lattice [1]. High-resolution image recording for single particle analysis with wide field of view cameras is also necessary to image a suitably large number of particles for reconstruction.…”
Section: Introductionmentioning
confidence: 99%